Crystal‐size–dependent external surface diffusion barriers in Pt/ZSM‐5 catalyzed n‐pentane isomerization. Issue 7 (30th March 2022) - Hu, Shen; Chen, Jiaxuan; Zhang, Qunfeng; Liu, Junru; Meng, Jinlin; Ye, Guanghua; Zhou, Xinggui; Yuan, Weikang
Abstract: Surface barriers persist in the molecular transport across external crystal surface of zeolites, which brings strong influences on zeolite catalysis. This study probes the role of crystal‐size–dependent surface barriers in zeolite catalysis, with n ‐pentane isomerization catalyzed by Pt/ZSM‐5 as a model reaction system. Chemical liquid deposition of SiO2 is performed to reduce surface barriers on ZSM‐5 crystals with different sizes. After SiO2 deposition, surface barriers on both small (266 nm) and large (1304 nm) crystals are significantly reduced, while the improvement in catalytic activity for the large crystals (76.1%–129.1%) is much higher than that for the small ones (−17.4% to 16.7%). For the large ZSM‐5 crystals, diffusion limitation is stronger, and thus the effect of surface barriers on catalytic activity is more important. This study reveals the unique role of crystal‐size–dependent surface barriers in zeolite catalysis, and understanding this is important for the optimal design of zeolite catalysts.